Recommendations for reproducibility of cerebrospinal fluid extracellular vesicle studies - International Society for Extracellular Vesicles Cerebrospinal Fluid Task Force (2024)
Funding Information: The authors are grateful to the respondents of the ISEV CSF Task Force survey, the time and efforts of the Task Force team members, and the members who provided feedback and edits for the final manuscript. This work was funded by NIH RF1 AG059392 (JAS), OHSU Center for Women's Health Circle of Giving (JAS, USS), R01 AG079356 (JAS); NIH RF1 AG054199 (TI), R01 AG066429 (TI), R01 AG067763 (TI); Fundação para a Ciência e a Tecnologia, I.P., through iNOVA4Health (UIDB/04462/2020, UIDP/04462/2020) and the LS4FUTURE Associated Laboratory (LA/P/0087/2020) (JC). Funding Information: The authors are grateful to the respondents of the ISEV CSF Task Force survey, the time and efforts of the Task Force team members, and the members who provided feedback and edits for the final manuscript. This work was funded by NIH RF1 AG059392 (JAS), OHSU Center for Women's Health Circle of Giving (JAS, USS), R01 AG079356 (JAS); NIH RF1 AG054199 (TI), R01 AG066429 (TI), R01 AG067763 (TI); Fundação para a Ciência e a Tecnologia, I.P., through iNOVA4Health (UIDB/04462/2020, UIDP/04462/2020) and the LS4FUTURE Associated Laboratory (LA/P/0087/2020) (JC). Publisher Copyright: © 2023 The Authors. Journal of Extracellular Vesicles published by Wiley Periodicals LLC on behalf of International Society for Extracellular Vesicles.